Pengaruh Pelayanan Informasi Obat (PIO) Terhadap Kepatuhan Pasien Tuberkulosis Paru di Puskesmas Sosial Palembang - Reza Agung Sriwijaya; Yenni Sri Wahyuni; Anggi Ramadani (PT FORMOSA CENDEKIA GLOBAL, 2022)
Drug Information Service (PIO) is an activity of providing and providing information, drug recommendations that are independent, accurate, unbiased, current, and comprehensive carried out by pharmacists to doctors, pharmacists, nurses, other health professionals as well as patients and other parties. To improve patient compliance, it can be done by providing drug information services (PIO). This study aims to determine the effect of PIO on the level of compliance of tuberculosis patients at the Palembang Social Health Center. This study used a Nonrandomized Control Group Pretest Posttest design which consisted of two groups, namely before PIO and after PIO. Data was obtained from the MMAS-8 questionnaire, sampling was carried out prospectively based on inclusion and exclusion criteria during February – March 2020 and analyzed using the Wilcoxon test. The samples obtained were 36 patients. The results showed that as many as 72.9% of tuberculosis patients were male and 27.0% female. A total of 40.5% were aged 25-44 years, aged 60 years were 21.6%. The percentage of patients complying before PIO high adherence 27.7%, moderate adherence 27.7%, and low adherence 44.4%. The percentage of patients who comply after PIO is high adherence 52.7%, moderate adherence 44.4% and low adherence 8.3%. Based on the Wilcoxon test, the value of p = 0.046 (<0.05) so that the provision of drug information services has a significant effect on the level of compliance of tuberculosis patients at the Palembang Social Health Center.